ANALYZING THE FINANCIAL PERFORMANCE OF PT. GARUDA INDONESIA BY USING DUPONT ANALYSIS (PERIOD 2011 – 2015) - Jasriani, Sahni (Sam Ratulangi University, 2016)
Commercial aviation is a part of aviation industry which specializes in operating aircraft for passengers and cargo. In Indonesia, there is one flag carrier that has a worldwide reputation in aviation industry which is Garuda Indonesia. PT. Garuda Indonesia is an Indonesia-based company primarily engaged in commercial airline business. This research aims to investigate the financial performance of PT. Garuda Indonesia for the period 2011-2015 by using DuPont analysis. This research uses descriptive type of research. The data required in this research is collected based on secondary data. The result suggests that the financial performance of PT. Garuda Indonesia for the last 5 years can generally considered bad. The financial ratio based on the return on equity ratio shows the ability of PT. Garuda Indonesia to increase its ROE (return on equity). Average of total ROE of PT. Garuda Indonesia for the last 5 years is -0.6% it means that PT. Garuda Indonesia’s financial performance are bad. In the period of 2011 – 2015, the best financial performance of PT. Garuda Indonesia was in 2012 when the number of ROE reached the highest number at 16.0%. In the last 5 years PT. Garuda Indonesia experience once significant performance degradation in 2014, where the number of total operating expenses were higher than the total operating revenues. This means the net income was not able to cover its expenses at that time. The increasing in the number of passengers, the production capacity and the amount of cargo affect biggest part of financial performance of PT. Garuda Indonesia. Therefore PT. Garuda Indonesia should focus on increasing the frequency of flights on both domestic and international as well as maintaining the level of accuracy of the flight (on time performance / OTP) to improve the financial performance of PT. Garuda Indonesia. Since there were some unfavorable events such as declining of the financial performance of PT. Garuda Indonesia caused by the rising of the fuel prices, the depreciation of Rupiah exchange rate against US Dollar and the slow development of the national air transport infrastructure, it is better for the firm to set the new strategy to avoid any significant changes toward those factors.